Presumed generalised seizure following caudal epidural administration of morphine and detomidine in a pony. (26th July 2020) - Tallon, R.; McMillan, M.; Ho, N.; Dunkel, B.
Summary: A 9‐year‐old show pony mare became acutely lame following removal of a bone sequestrum of the distal phalanx of the right thoracic limb. The mare also suffered from ongoing right dorsal colitis secondary to previous long‐term nonsteroidal anti‐inflammatory drug (NSAID) use. To avoid further NSAID use, a protocol for caudal epidural administration of morphine and detomidine in an increased volume was used to provide analgesia to the thoracic limbs. A total volume of 50 mL (0.2 mL/kg bwt) was administered over approximately 90 s. Immediately following the injection, the pony collapsed into lateral recumbency and experienced an apparent generalised seizure characterised by loss of consciousness and frantic paddling of all four limbs. The pony recovered rapidly without intervention, and no residual neurological deficits were noted. The epidural analgesia resulted in a marked improvement in comfort levels. The speed of injection is thought to have caused a change in epidural and intracranial pressures resulting in a generalised seizure and highlights the importance of administering large volumes slowly.